A facile, rapid, one-pot regio/stereoselective synthesis of 2-iminothiazolidin-4-ones under solvent/scavenger-free conditions - Sathishkumar, Murugan; Nagarajan, Sangaraiah; Shanmugavelan, Poovan; Dinesh, Murugan; Ponnuswamy, Alagusundaram (Beilstein Journal of Organic Chemistry, 2013)
A rapid and efficient one pot solvent/scavenger-free protocol for the synthesis of 2-iminothiazolidin-4-ones has been developed. Interestingly, the regio/stereoselective synthesis affords the regioisomeric (Z)-3-alkyl/aryl-2-(2-phenylcyclohex-2-enylimino)thiazolidin-4-one as the sole product in good yield. The selectivities observed have been rationalized based on the relative magnitude of the allylic strains developed during the course of the reaction. This is the first report wherein the impact of allylic strains in directing the regiocyclization has been noted.
Keywords: 2-iminothiazolidin-4-ones; regioselective; stereoselective; solvent-free; scavenger-free